P203 Late failure of NIV in exacerbations of COPD: all is not lost. (December 2018) - Hartley, TM; Lane, ND; Steer, J; Bourke, SC
Abstract : Introduction: Late failure (LF) of NIV is initial success (correction of respiratory acidaemia) but subsequent deterioration, rise in PaCO2 and recurrence of respiratory acidaemia while still in receipt of NIV. Moretti 1 reports 31/137 (23%) patients with COPD exacerbation (ECOPD) experienced LF who, based on patient preference, received either invasive ventilation (n=19, in-hospital mortality 53%) or increased duration of NIV (n=12, in-hospital mortality 92%). These results have influenced international guidance. Methods: Consecutive, unique patients hospitalised with a primary diagnosis of spirometry confirmed ECOPD requiring NIV were identified (NIV Outcomes study derivation cohort). Late failure was defined as: ' Recurrence of respiratory acidaemia prior to discontinuation of ventilation. pH should drop to below 7.35 with a rise in CO2 of at least 1 kPa and to >6.0 kPa from the lowest recorded post pH correction at least 24 hours after pH correction .' Results: 35/489 (7.2%) patients hospitalised between Dec-2008 and May-2013 experienced LF; none were intubated, 3 were immediately palliated and a further 5 had NIV withdrawn within 24 hours. Excluding 3 immediately palliated, NIV was provided for mean 12.4/24 hour pre LF and 17.1/24 hour post. Median pressures were modestly increased from median 18/4 to 20/5. Overall inpatient mortality was 25.4%. Discussion: Development of LF was associated with an increased mortality, but 2/3 survived to discharge with optimised NIV, compared to only 8% in previously reported results. Patients developing LF had higher eMRCD score and trended toward increased LTOT prescription and later acidaemia development. LF was not associated with greater physiological burden as measured by the APACHE II score. At time of presentation comparison results from 10 UK centres n=734 NIVO validation study will be available. Reference: Moretti, et al. Thorax2000;55(10):819–25.